Effects of folic acid supplementation before conception on innate immunity and anti-HBs levels of offspring born to HBsAg-positive mothers - Lian, Jia; Men, Zhaoyue; Xu, Xiuyang; Li, Yandi; Li, Jinbo; Wang, Weigang; Yao, Tian; Li, Yuping; Qu, Yiqun; Feng, Yongliang; Wang, Suping (Frontiers in Nutrition, 2025)
IntroductionFolic acid has been associated with fetal development, especially in fetal immunity. Therefore, limited evidence regarding the effects of different folic acid supplementation of hepatitis B surface antigen (HBsAg) positive mothers in innate immunity in offspring. Herein, this study aimed to explore the association between folic acid supplementation and the innate immunity of neonates and the immunological efficacy of hepatitis B vaccine (HepB), which may provide insights that could inform pre-pregnancy health management in HBsAg-positive mothers.Materials and methodsIt is an ambispective cohort study with 293 pairs of HBsAg-positive mothers-offspring in Taiyuan, Shanxi Province, China. Mothers were classified into three groups according to the time of starting folic acid supplementation, non-supplementation group, pre-pregnancy group and post-pregnancy supplementation group. Immunological indexes such as immune cells proportion and innate immune mediators in cord blood and anti-HBs in infants were measured. Differences in immunological indexes were analyzed by One-Way ANOVA test. Univariate and multivariate analyses were performed for factors associated with abnormal immunological indexes and potential confounders were adjusted.ResultsThe preconception folic acid group showed a significantly higher expression levels of STING (P = 0.005) and pNF-κB (P = 0.010) in cord blood along with higher anti-HBs titres (P = 0.006), when compared to both non-supplementation group and post-pregnancy supplementation group. Higher anti-HBs levels indicate a stronger immune response to HepB and may enhance protection against HBV infection during early life. Infants in the high pNF-κB expression group exhibited a significantly elevated seropositive rate of HepB compared to those in the low pNF-κB expression group (P = 0.037). There were no mediation effects and no moderation effects in this study, potentially due to the direct influence of folic acid supplementation on immune responses or the limited sample size.DiscussionIn conclusion, our findings demonstrate that preconception folic acid supplementation may enhance HepB vaccine responsiveness in infants of HBsAg-positive mothers. Meanwhile, high pNF-κB expression in cord blood can increase seropositive rates in infants. This discovery has significant public health implications, as it may provide a simple and accessible intervention to improve vaccination outcomes and reduce HBV transmission in endemic regions.